Silent presentation of multiple metastasis Burkitt lymphoma in a child: A case report and review of the literature - Miron, Ingrith (Medicine (Baltimore), 2017)
RATIONALE: The Burkitt lymphoma (BL) is a very aggressive B-cell non-Hodgkin's lymphoma. It accounts for 34% of lymphoma cases in children. PATIENT CONCERNS: We present the case of a 6-year-old boy diagnosed with BL, who presented multiple contrasting elements of the disease: silent symptomatology, without involvement of the bone marrow at first, but with multiorgan infiltration and a fast evolution, despite starting the treatment shortly after the symptoms appeared. DIAGNOSES: He was diagnosed with BL after immunophenotyping from the pleural fluid. INTERVENTIONS: After a week from admission, chemotherapy was initiated according to protocol NH-BFM therapeutic group III—cytoreductive phase in the acute care ward and subsequently the AA 24 treatment. OUTCOMES: Following the treatment, the patient developed medullary aplasia and cutaneous toxicity. The patient's general state remained severe during the hospitalization. LESSONS: Even though the prognosis of BL has improved over time (up to 90% survival rate), in this case the evolution was unfavorable. In our patient, the symptoms appeared abruptly. They appeared late in the phase of multiple-organ dissemination, which generated the pessimistic prognosis.